Handbook of Additive Manufacturing (AM) adoption - Jussila, Maria; Eriksson, Taina (Turun yliopisto, 2025)
Additive Manufacturing (AM) has emerged as a transformative technology reshaping industries worldwide. While its potential for innovation and efficiency gains are widely acknowledged, the journey toward implementing AM within organizations is fraught with challenges that extend beyond technical considerations. This handbook serves as a comprehensive guide to navigating the complexities of AM adoption, offering insights, strategies as well practical guidance for managers and other experts to facilitate successful AM implementation into organizational practices.